The Impact of True or False Type Active Learning Strategy with AI and Motivation on Student Learning Activities at MTsN Medan - Sinaga, Putri Wahyuni; Nasution, Toni (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to enhance student participation in learning. The research was conducted from May 2024 to June 2024 at MTsN 1 Medan. This study employs a quantitative method with an experimental approach. This approach allows for testing the effect of independent variables on dependent variables. The subjects of the study were students from class VII4 and VII5 at MTsN 1 Medan. The testing involved 36 students from VII4 and 36 students from VII5 at MTsN 1 Medan. The research conducted shows that there is a difference after implementing the True or False type active learning strategy, combined with artificial intelligence (AI) and learning motivation for the students. Pre-test and post-test were administered, followed by normality tests, homogeneity tests, and t-tests. The normality test shows a Kolmogorov-Smirnov sig value > 0.05, indicating that the data is normally distributed. The homogeneity test shows a sig value Based on Mean of 0.06 > 0.05, indicating homogeneity. The t-test results show that the data for the experimental class pretest and posttest, as well as for the control class pretest and posttest, yield significant values <0.001, which are less than 0.005.